Tumor microenvironment-responsive micelles assembled from a prodrug of mitoxantrone and 1-methyl tryptophan for enhanced chemo-immunotherapy. (31st December 2023) - Wang, Ru; Li, Nuannuan; Zhang, Tianyu; Sun, Yiying; He, Xiaoyan; Lu, Xiaoyan; Chu, Liuxiang; Sun, Kaoxiang
Abstract: Mitoxantrone (MX) can induce the immunogenic-cell death (ICD) of tumor cells and activate anti-tumor immune responses. However, it can also cause high expression of indole amine 2, 3-dioxygenase (IDO) during ICD, leading to T-cell apoptosis and a weakened immune response. An IDO inhibitor, 1-methyl tryptophan (1-MT), can inhibit the activity of IDO caused by MX, resulting in enhanced chemo-immunotherapy. Here, MX-1-MT was connected by ester bond which could be broken in an acidic tumor microenvironment. MX-1-MT was combined with polyethylene glycol (PEG) via a disulfide bond which could be reduced by glutathione overexpressed in tumors, thereby accelerating drug release at target sites. Folic acid-modified distearoyl phosphoethanolamine-polyethylene glycol (DSPE-PEG-FA) was introduced to form targeting micelles. The micelles were of uniform particle size, high stability, and high responsiveness. They could be taken-up by drug-resistant MCF-7/ADR cells, displayed high targeting ability, and induced enhanced cytotoxicity and ICD. Due to 1-MT addition, micelles could inhibit IDO. In vivo studies demonstrated that micelles could accumulate in the tumor tissues of nude mice, resulting in an enhanced antitumor effect and few side-effects.